2019
DOI: 10.1186/s12263-019-0653-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of PPARγ in childhood obesity-induced fractures

Abstract: Globally, obesity is on the rise with ~ 30% of the world’s population now obese, and childhood obesity is following similar trends. Childhood obesity has been associated with numerous chronic conditions, including musculoskeletal disorders. This review highlights the effects of childhood adiposity on bone density by way of analyzing clinical studies and further describing two severe skeletal conditions, slipped capital femoral epiphysis and Blount’s disease. The latter half of this review discusses bone remode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 97 publications
(98 reference statements)
0
4
0
Order By: Relevance
“…According to their different structures, PPARs can be divided into three types α, β, and c. Among them, PPARc is mainly expressed in adipose tissue and the immune system, which has adipose tissue specificity, and can regulate the expression of lipid metabolism enzymes. It plays an important regulatory role in adipogenic differentiation [12]. Lipid droplet coating protein perilipin is an important protein that regulates lipolysis and plays an important role in lipolysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…According to their different structures, PPARs can be divided into three types α, β, and c. Among them, PPARc is mainly expressed in adipose tissue and the immune system, which has adipose tissue specificity, and can regulate the expression of lipid metabolism enzymes. It plays an important regulatory role in adipogenic differentiation [12]. Lipid droplet coating protein perilipin is an important protein that regulates lipolysis and plays an important role in lipolysis [13].…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, it is important to note that obesity is a condition associated to a disturbed muscle and bone physiology, together with higher intramuscular fat deposition and osteoporosis. 88,89 This suggests that proper development of these tissues may also be disturbed in utero. Also, this raises the question of whether other stem cell lineages could be compromised: are ectodermal and endodermal lineages altered by maternal obesity?…”
Section: Discussionmentioning
confidence: 99%
“…Could this result in a decreased differentiation towards muscle, bone and cartrilage cells? In this respect, it is important to note that obesity is a condition associated to a disturbed muscle and bone physiology, together with higher intramuscular fat deposition and osteoporosis 88,89 . This suggests that proper development of these tissues may also be disturbed in utero.…”
Section: Discussionmentioning
confidence: 99%
“…Although, the data suggest that the ATX-LPA axis reduces PPAR-c function, the specific mechanisms by which it contributes to obesity remains to be elucidated (Jose and Kienesberger 2021). In contrast, it has been reported that obese individuals have higher PPAR-c mRNA levels, which contributes to an increase in the numbers of adipocytes (Vidal-Puig et al, 1997;McCann and Ratneswaran 2019). Interestingly, activation of PPAR-c induces an increase in the number of small and insulin-sensitive adipocytes and upregulates adiponectin, improving insulin sensitivity in the liver and muscle (Jakab et al, 2021).…”
Section: Lysosomal Dysfunction In Obesity Role Of Cd36 In Adipocytes and Hepatocytesmentioning
confidence: 99%